Sion sebagai Pusat Kerajaan (tidak) Damai: Membaca Yesaya 2:1-4 dari Konteks Indonesia - Jusuf Haries Kelelufna (Sekolah Tinggi Teologi Berita Hidup, 2023)
Various interpretive tendencies towards the text of Isaiah 2:1-4 that exist today emphasize the physical and eschatological aspects of Israel's restoration. Efforts to realize the prophecy in Israel have contributed to the rise of radicalism in Indonesia. This paper aims to answer several questions in the text read from the Indonesian context, namely: what is the relevance of rebuilding the Temple? What is the truth of God's word? And is Jerusalem really the center of peace? This research was conducted with an exegesis approach and library research. The results of exegesis are critically reciprocally dialogued with the Indonesian context using related literature studies. The results of the analysis show the relationship between rebuilding the temple of God and building churches in Indonesia, the validity of the truth of God's word in Indonesia is based on pragmatic proof of the truth, and Indonesia as a Center for Peace. The findings of this study encourage action plans, among others; intensify inter-religious dialogue starting from the level of religious figures to the lower level of the community and encourage moderate religious life. It needs the openness of various parties in the development of the study of Bible interpretation as well as adjustments to various methods of interpretation that continue to develop, as well as seeking practical forms of Indonesia's involvement in creating world peace.